The relationship between knowledge management approaches and job satisfaction among the government servant at Pejabat Pendidikan Daerah, Kelantan / Faizatul Fariza Moh Pasuzi - Moh Pasuzi, Faizatul Fariza (2015)
Knowledge has been recognized as valuable organizational resources from strategic perspectives (James, 2004) and a foundation for competitive advantage in today 's business environment (Erden et al., 2008). The aim of this study is to investigate the influence of knowledge management approaches (Knowledge Acquisition, Knowledge Conversion, Knowledge Application, Knowledge Storing and Knowledge Protection) on employee 's job satisfaction. It is widely accepted that knowledge management is critical success for the organization performance. A number of 118 employees from Pejabat Pendidikan Daerah in Kelantan were chosen using stratified sampling and the data were analyzed using Statistical Package for Social Sciences (SPSS), version 20.0. SPSS purposely used to provide a broad range of capabilities for the entire analytical process. The results showed that only Knowledge Application and Knowledge Protection have significant factor loading on Job Satisfaction. Meanwhile for the Knowledge Acquisition, Knowledge Conversion and Knowledge Storing have less significant and no correlated with Job Satisfaction. However, the Knowledge Management approaches does not implement well in the organization due to the lack of encouragement and support from the organization.